Cutaneous malignant melanoma in Scotland. - MacKie, R. M. (Nature Publishing Group, 1982)
In view of the concern over the rising incidence of malignant melanoma in many parts of the world, and the suggestion that emigrants of Scottish and Irish descent have a higher incidence of melanoma in North America and Australia, a Scottish Melanoma Group has been formed to study epidemiological, pathological and therapeutic aspects of the tumour. In 1979, 260 histologically proven primary cutaneous malignant melanomas of the skin presented. This represents an incidence of 5.1/10(5) for Scotland as a whole. Studies over the next 5 years will determine whether the incidence of melanoma is rising in Scotland as rapidly as in other parts of the world.